The national system of education in Cuba: an approach to their current state and perspectives - Jorge Alejandro Laguna Cruz; Alba Sánchez Arencibia (ADIDE Federación, 2015)
In the article the authors carry out a valuation, from several aspects of historical character, of the current state and future of the National System of Education (SNE) of Cuba. The Cuban SNE is universal, public and gratuitous, fruit of the deep social Revolution that the country has lived from 1959. The objectives and fundamental principles of this SNE has been countersigned by the Constitution of the Republic, effective from February 24 1976 and modified in 1992, being included in several of its Chapters and articles. At the present time, result of an adverse economic situation that the country has lived from final of the XX century, generated by the loss of the traditional export markets, the fall of the PIB in 34.8% and the worsening of economic measures on the part of the government of EE. UU, negative effects have taken place in the SNE, taking to the authorities to restate of political and actions to attenuate their consequences, for what they are carried out different investigations in several Universities.